Glucagon-like peptide-1 receptor-agonists treatment for cardio-metabolic parameters in schizophrenia patients: a systematic review and meta-analysis - Khaity, Abdulrhman; Mostafa Al-dardery, Nada; Albakri, Khaled; Abdelwahab, Omar A.; Hefnawy, Mahmoud Tarek; Yousef, Yaman A. S.; Taha, Ruaa E.; Swed, Sarya; Hafez, Wael; Hurlemann, Rene; Elsayed, Mohamed E. G. (Frontiers in Psychiatry, 2023)
Aims: We performed this meta-analysis to evaluate the efficacy and safety of glucagon-like peptide-1 receptor-agonists (GLP-1RA) treatment on cardio-metabolic parameters among antipsychotic‐treated patients with schizophrenia. Methods: We searched the Web of Science, Cochrane Central Register of Controlled Trials, PubMed, PsycINFO, and Scopus for relevant Randomized Clinical trials (RCTs) from inception until 1 August 2022. Documents were screened for qualified articles, and all concerned outcomes were pooled as risk ratios (RR) or mean difference (MD) in the meta-analysis models using Review Manager (RevMan version 5.4). Results: Pooling data from 7 RCTs (398 patients) showed that GLP-1 RA was superior to placebo with regard to body weight (MD = - 4.68, 95% CI [-4.90, -4.46], P < 0.00001), waist circumference (MD = - 3.66, 95% CI [-3.89, -3.44], P < 0.00001), body mass index (BMI) (MD = - 1.09, 95% CI [-1.25, -0.93], P < 0.00001), systolic blood pressure (SBP) (MD = - 3.07, 95% CI [-3.61, -2.53], P < 0.00001), and diastolic blood pressure (DBP) (MD = - 2.02, 95% CI [-2.42, -1.62], P < 0.00001). The total effect did not favor either of the two groups in respects of insulin and respiratory adverse events ((MD = - 0.06, 95% CI [-0.36, 0.24], p = 0.70), (RR = 0.66, 95% CI [0.31, 1.40], p = 0.28); respectively). Conclusion: Our analysis revealed that GLP-1 RA treatment is safe and effective on cardio-metabolic parameters over control in antipsychotic‐treated patients with schizophrenia. Nevertheless, the present evidence is not sufficient to confirm the safety and efficacy of GLP-1 receptor-agonists treatment on insulin and respiratory adverse events. Therefore, further studies are recommended.